Primary care perceptions of neurology and neurology services. Issue 1088 (20th January 2016) - Loftus, Angela M; Wade, Carrie; McCarron, Mark O
Abstract: Background: Neurophobia (fear of neural sciences) and evaluation of independent sector contracts in neurology have seldom been examined among general practitioners (GPs). Methods: A questionnaire determined GPs' perceptions of neurology compared with other medical specialties. GP experiences of neurology services with independent sector companies and the local National Health Service (NHS) were compared. Areas of potential improvement in NHS neurology services were recorded from thematic analyses. Results: Among 76 GPs neurology was perceived to be as interesting as other medical specialties. GPs reported less knowledge, more difficulty and less confidence in neurology compared with other medical specialties. There was a preference for a local NHS neurology service (p<0.001), which was easier to contact (p<0.001) and provided better follow-up. GPs reported that local neurology services provided better patient satisfaction. Conclusions: GPs prefer local NHS neurology services to independent sector contracts. GPs' evaluations should inform commissioning of neurology services. Combating neurophobia should be an integral part of responsive commissioning.